The relationship between death anxiety and self-esteem: A protocol for a systematic review and meta-analysis - Tadgh Connery; Sofija Kukulite; Conor Farrell; Rosa Horgan; Karen Barry; Megan Doyle; Annalisa Setti; Mike Murphy (PLoS ONE, 2026)
Background Death anxiety is fast becoming recognised as a transdiagnostic construct across myriad mental health conditions. Though existing clinical treatments of death anxiety, such as Cognitive Behaviour Therapy type interventions, have been shown to be effective, Terror Management Theory (TMT) proposes self-esteem as a protective factor against death anxiety by endowing individuals with a feeling of significance in life and helping them to process the nature of death and its inevitability. Despite the centrality of self-esteem to TMT, however, extant research examining its relationship with death anxiety has yet to be synthesised. The current study aims to systematically review peer-reviewed, quantitative research examining the association between death anxiety and self-esteem and, where possible, to test the strength of these associations through meta-analysis. Method A systematic search of quantitative and mixed-methods studies will be conducted across six databases: MEDLINE; PsycINFO; PubMed; Web of Science; CINAHL and; EMBASE. Google Scholar will also be searched and the first 200 records by relevance will be screened for eligibility. Searches will be conducted by TC, and records will be screened by TC, SK, CF, RH and KB, so that each record is screened for eligibility by at least two authors. Data extraction and quality assessment, using the Joanna Briggs Inventory Risk of Bias tools, will be performed by TC, SK, CF, RH and KB, so that each record is assessed by at least two authors, with doubts and discrepancies being resolved through discussion with AS and MM. A narrative synthesis of relevant data will be presented and, where sufficient data are available, meta-analysis will be conducted using the MAJOR extension for Jamovi to establish an overall effect size for the association between death anxiety and self-esteem. Should sufficient data be available, demographic factors, such as gender and age, and clinical population status (clinical vs. non-clinical population) will be examined as moderators of the effect. This protocol was developed in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and has been registered in PROSPERO (CRD42024591775). Discussion The current review will systematically examine the relationship between death anxiety and self-esteem. Should sufficient data be available, an overall effect size of the relationship will be generated. By better understanding how death anxiety is related to self-esteem, and by establishing the size and significance of the relationship will aid firstly in systematically validating TMT and, secondly, identify whether self-esteem may be targeted in future death anxiety interventions to reduce death anxiety and improve individuals’ overall mental health.